2015 Social Accounting Matrix for Egypt - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The Regional 2014/15 SAM for Egypt includes 62 sectors and 66 products. It also includes 13 factors of production, labor is disaggregated across rural and urban areas and into four education-based categories, capital is also disaggregated into four subcategories: crops, livestock, mining, and other; and land. Moreover, the new SAM has 105 household groups that are disaggregated by national per capita expenditure quintiles, then split into national rural farm, rural nonfarm, and urban households. Sectoral production, factor markets, and household groups are split into seven subnational regions: Greater Cairo, Delta, Alexandria, Northern Upper Egypt, Middle Upper Egypt, Southern Upper Egypt, and Suez Canal. In total, the regional 2015 SAM is composed of 646 rows x 646 columns.